Erosão hídrica e infiltração de água em diferentes sistemas de manejo de solo e cultivos. - Nelson Otávio da Motta Vieira (2020)
Population growth drives increased consumption and, consequently, demand for agricultural production. However, the agricultural sector has been considered a villain with regard to water consumption. When questioning water consumption in livestock, in general, factors such as the potential for infiltration and evapotranspiration are not mentioned. To answer this question, studies related to such factors will be necessary. The purpose of this work is to evaluate if there is an influence of the cultivation and soil management system on the infiltration of water in the soil. We assume that the vegetation cover on the surface, in association with grazing and cultivation systems, integrated crop rotation, livestock and forest production, alters soil and water losses and the rate of water infiltration into the soil. We evaluated potential correlations between soil attributes and infiltration rates and the performance of infiltration rate models. Analyzing the Kostiakov-Lews, Horton and Philip models, we see that Philip's presents better performance, followed by Horton and finally Kostiakov-Lews to estimate the infiltration rate. However, the Kostiakov-Lews model is advantageous because it is semi-empirical and simpler than Horton's. We propose an innovative model, of conversion into infiltration rates with vegetation cover into infiltration rates without cover and vice versa. The proposed model was based on the Kostiakov-Lewis model, showing performance similar to other conversion models, being effective in any planting and vegetation cover system.